Cloning and expression of prM and it's use to distinguish host immune responses against dengue virus and Japanese encephalitis virus infections - Wang, Seok Mui (2001)
All flaviviruses share common epitopes on the envelope protein (E) that results in extensive crossreactions in serological tests. /this makes it difficult to distinguish between immune responses against dengue virus (DENV) and Japanese encephalitis virus (JEV), particularly in regions where these viruses co-circulate. We have demonstrated that DENV and JEV have unique epitopes on the prM. By detecting prM specific IgG, it is possible to distinguish between DENV and JEV infection. Current approach used in seroanalysis of DENV and JEV infections is based on antigens derived from the whole viral antigens.